Tactics for hemorrhagic shock: A virtual course and visual aid for improved resuscitation. Issue 6 (4th December 2022) - Keating, Jane Josephine; Silvis, Jennifer; Ricaurte, Daniel; Desrochers, Ryan; Jacobs, Lenworth; Saccomanno, Fabio; Staff, Ilene; Croteau, Alfred; Merchant, Nishant; Gates, Jonathan
Abstract : From the same center that brought you #StoptheBleed and the ATOM course, @HartfordTrauma presents: "TACTICS for Hemorrhagic Shock, " a virtual course and visual aid designed to enhance patient care and trauma education. Abstract : BACKGROUND: Our trauma performance improvement initiative recognized missed treatment opportunities for patients undergoing massive transfusion. To improve patient care, we developed a novel cognitive aid in the form of a poster entitled "TACTICS for Hemorrhagic Shock." We hypothesized that this reference and corresponding course would improve the performance of trauma leaders caring for simulated patients requiring massive transfusion. METHODS: First, residents and physician assistants participated in a one-on-one, socially distanced, screen-based virtual patient simulation. Next, they watched a short presentation introducing the TACTICS visual aid. They then underwent a similar second virtual simulation during which they had access to the reference. In both simulations, the participants were assessed using a scoring system developed to measure their ability to provide appropriate predetermined interventions while leading a trauma resuscitation (score range, 0–100%). Preintervention and postintervention scores were compared using a one-group pre-post within-subject design. Participants' feedback was obtained anonymously. RESULTS: Thirty-two participants (21 residents and 11 physician assistants) completed the course. The median score for the first simulation without the use of the visual aid was 43.8% (interquartile range, 33.3.8–61.5%). Commonly missed treatments included giving tranexamic acid (success rate, 37.5%), treating hypothermia (31.3%), and reversing known anticoagulation (28.1%). All participants' performance improved using the visual aid, and the median score of the second simulation was 89.6% (interquartile range, 79.2–94.8%; p < 0.001). Ninety-two percent of survey respondents "strongly agreed" that the TACTICS visual aid would be a helpful reference during real-life trauma resuscitations. CONCLUSION: The TACTICS visual aid is a useful tool for improving the performance of the trauma leader and is now displayed in our emergency department resuscitation rooms. This performance improvement course, the associated simulations, and visual aid are easily and virtually accessible to interested trauma programs. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level IV. Abstract :